DEVELOPMENT OF MATHEMATICS LEARNING MEDIA BASED ON INTERACTIVE MULTIMEDIA USING MACROMEDIA FLASH 8 SUBSIDIARIES OF TWO VARIABLES LINEAR EQUATION SYSTEM FOR CLASS VIII MIDDLE SCHOOL - Arief Rahman; Widayati Widayati (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
Media developed learning because students are still difficult to understand the material system of linear equations so that the need for renewable innovations in mathematics for students in learning to overcome boredom. The research aims to develop and test the feasibility of learning media in the form of interactive multimedia using Macromedia Flash 8 in mathematics learning in junior high school in the material Linear Equation System Two Variables. This study focused on the development of mathematics learning media is packaged in a Compact Disc (CD). The development of research using the ADDIE development model that is Analysis, Design, Development, Implementation, and Evaluation. Penilitiannya are subject matter experts, media experts and SMP N 4 Banguntapan and SMP Muhammadiyah 17 Prambanan Klaten. Learning media is validated by 3 votes materials experts, 3 experts media, and the subject of the trial of 10 students on a test smaller classes and all students in the pilot class of great use assessment instruments or sheets instrument quality research materials and instructional media and student response, This research has successfully developed a mathematics learning media that have quality Good (B). With an average score of 76.67 matter expert assessment results and the average score of 40.33 media expert assessment results. While the score student responses with a score of 69.74 in the trials and testing of small class large class. So that the average score of 186.74 ideals percentage of the maximum score of 225 is ideal ideals with a percentage of 82.99%. Based on these assessments, then the media is worth the learning of mathematics is used as a learning resource for students.